Estado cognitivo y funcionalidad familiar de los adultos mayores de la Zona 7. Ecuador, 2016. - Tigre Bueno, Jaime Oswaldo (2017)
Family dynamics are an important part of the health-disease process within the elderly, with cognitive impairment forming an important part in assessing their fragility. Family functionality was considered problematic and also as an important factor in the cognitive situation of the elderly. This cross-sectional research studied the relationship between cognitive status and family functionality of senior citizens aged 65 years or older from Zone 7 in Ecuador. The general objective of this study was to determine the cognitive status of the elderly and its relation to family functionality. The hypothesis mentions that there is a relationship between the familiar functionality and the cognitive impairment. The sample comprised 1,146 senior citizens distributed among the three provinces of Zone 7: Loja 395, El Oro 385 and Zamora Chinchipe 366. A stratified random sampling was employed. Data-collection instruments were used to collect socio-demographic data, The Pfeffer Functional Activity questionnaire (FAQ) was used for the detection of older adults’ cognitive function and the test of perception of family functioning (FF-SIL) was used as well. Men, who were predominantly 65-74 years old, mixed race, married, and from an urban origin, form the largest part of the elderly population in Zone 7 of Ecuador. Older adults live in small, nuclear families in the process of contraction and dissolution. The prevalence of cognitive impairment was 25.48%. The prevalence of severe family dysfunction was 14,57%. A statistically significant correlation was found between cognitive impairment and family dysfunction (OR 1,66;) 95% 1,27 – 2,17; p<0,05. In conclusion, this association results in a family health problema that must be prioritized by health services. Key words: elderly, familiy, cognitive impairment, family dysfunction.